The comparison of adsorption characteristics of CO2/H2O and N2/H2O on activated carbon, activated alumina, zeolite 3A and 13X. (August 2022) - Lu, Junhui; Tang, Jinjing; Li, Junming; Wang, Suilin
Highlights: The adsorption of CO2 /H2 O and N2 /H2 O is compared by dynamic experiments. Effects of flow rate, temperature and steam mole fraction are analyzed. Activated carbon and activated alumina, zeolite 3A and 13X are compared. CO2 /H2 O adsorption selectivity ranked as: 3A> 13X> alumina> activated carbon. The thermal wave peak of N2 /H2 O is decayed and delayed comparing to CO2 /H2 O. Abstract: The breakthrough curves and adsorption amounts of N2 /H2 O and CO2 /H2 O on activated carbon, activated alumina, zeolite 3A and zeolite 13X were studied experimentally. The experiments were conducted to investigate the effects of inlet steam mole fraction, flow rate and temperature. The effect of steam mole fraction on the thermal effect of adsorption was also studied. The results show that the breakthrough time and adsorption saturation time of adsorbates are decreased with increasing flow rate and temperature. When steam mole fraction increases, the breakthrough time and adsorption saturation time of adsorbates on zeolite 3A and 13X are decreased, while these of other adsorbents are increased. As steam mole fraction increases from 1% to 2%, the adsorption amount of CO2 decreases by 2.2–45.4% and that of N2 decreases by 12.2–19.1%. Zeolite 3A shows a good adsorption selectivity for CO2 /H2 O and N2 /H2 O. The thermal wave peak time of N2 /H2 O is 0.71–8.31 min longer than that of CO2 /H2 O, while the peak temperature of N2 /H2 O is 2–16 °C smaller than that of CO2 /H2 O. As steam mole fraction increases from 1% to 2%, the peak temperature of CO2 /H2 O increases by 1.63–11.55 °C and N2 /H2 O increases by 2.17–18.17 °C. The thermal wave peak of N2 /H2 O and CO2 /H2 O on activated carbon adsorption bed is the smallest among these four adsorbents.